2022
DOI: 10.1038/s41420-022-01268-y
|View full text |Cite
|
Sign up to set email alerts
|

H3K27 tri-demethylase JMJD3 inhibits macrophage apoptosis by promoting ADORA2A in lipopolysaccharide-induced acute lung injury

Abstract: Acute lung injury (ALI) is a common critical disease, which is characterized by an uncontrolled, acute inflammatory response, diffuse lung damage and ultimately directly deteriorates into acute respiratory distress syndrome. The number of pro-inflammatory macrophages is related to the severity of ALI. Up-regulation of lipopolysaccharide (LPS)-activated macrophage apoptosis can reduce the pro-inflammatory reactions. Jumonji domain-containing protein D3 (JMJD3)-mediated histone 3 lysine 27 trimethylation (H3K27m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This is evidenced by our observations that inhibition of JMJD3 promoted the cleavage of caspase‐3, a key enzyme responsible for execution of apoptosis and Bax, a critical executioner of mitochondrial‐regulated cell death. In support of our observations, Jia et al also reported that JMJD3‐indued H3K27me3 demethylation inhibited caspase‐3 cleavage, decreasing LPS‐stimulated apoptosis of macrophages 35 ; Yang et al demonstrated that knockdown of JMJD3 promoted osteoblast apoptosis induced by serum deprivation with increased levels of caspase‐3 activation 36 . In the latter study, they also explored the mechanism of JMJD3 inhibition‐mediated caspase‐3 activation and apoptosis and found that JMJD3 contributes to expression of BCL2, a well‐known anti‐apoptotic protein and repression of Bim and Bax, two proapoptic proteins associated with disruption of mitochondrial membrane potential and cytochrome C release 36 .…”
Section: Discussionsupporting
confidence: 91%
“…This is evidenced by our observations that inhibition of JMJD3 promoted the cleavage of caspase‐3, a key enzyme responsible for execution of apoptosis and Bax, a critical executioner of mitochondrial‐regulated cell death. In support of our observations, Jia et al also reported that JMJD3‐indued H3K27me3 demethylation inhibited caspase‐3 cleavage, decreasing LPS‐stimulated apoptosis of macrophages 35 ; Yang et al demonstrated that knockdown of JMJD3 promoted osteoblast apoptosis induced by serum deprivation with increased levels of caspase‐3 activation 36 . In the latter study, they also explored the mechanism of JMJD3 inhibition‐mediated caspase‐3 activation and apoptosis and found that JMJD3 contributes to expression of BCL2, a well‐known anti‐apoptotic protein and repression of Bim and Bax, two proapoptic proteins associated with disruption of mitochondrial membrane potential and cytochrome C release 36 .…”
Section: Discussionsupporting
confidence: 91%
“…Acute lung injury (ALI) is a chronic clinical syndrome caused by serious inflammatory damage that could progress to life-threatening acute respiratory distress syndrome (ARDS) unless promptly treated [ 1 , 2 ]. The pathology of ALI is characterized by the activation and infiltration of inflammatory cells, respiratory distress, and diffuse pulmonary edema [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%